In Vivo and In Vitro Studies Assessing the Antiviral Efficacy of Double Combinations Against Coxsackievirus B Infection - Adelina Stoyanova; Simeon Galabov; Vadim Makarov; Angel S. Galabov (Microorganisms)
Coxsackievirus B (CVB) infections, ranging from mild to severe diseases, lack specific antiviral treatments, underscoring the need for novel therapeutic strategies. Drug therapy is an important tool for controlling enterovirus infections, but clinically effective drugs do not currently exist, mainly due to the development of drug resistance. Combination therapy with two or more drugs has the potential to successfully inhibit viral infection more effectively than either drug alone as well as delay the development of resistance. This study explores the consecutive alternating administration (CAA) scheme in mice with CVB1 infection, utilizing double antiviral combinations consisting of pleconaril and MDL-860, with guanidine hydrochloride and oxoglaucine. The CAA combinations of pleconaril achieved a survival rate, in infected mice, of up to 59%, while the combinations of MDL-860 showed no significant effects. CAA reduced mortality, prolonged mean survival time (up to 5 days), and mitigated drug resistance compared to monotherapy or simultaneous administration. Monotherapeutic courses and daily administration of double combinations had no effect. Phenotypic characterization using the IC50 marker of virus isolates from brain tissue of infected and treated mice was of particular importance for the evaluation of the CAA treatment scheme. The results show increased susceptibility of the virus isolates to the partner compounds in double CAA combinations. In contrast, virus isolates from the monotherapeutic groups manifested a diminished susceptibility to their respective compound, which signals the development of drug resistance. All data obtained prove the potential of the CAA scheme for the development of effective chemotherapy of enterovirus infections.